Analysis of BPJS patient satisfaction levels against pharmaceutical services in outpatient pharmacy installation of Anwar Medika Hospital - Ahmad Zulfikar Badri; Khurin In Wahyuni; Puspita Raras Anindita (Universitas Muhammadiyah Malang, 2021)
Good pharmaceutical services are directly oriented in using drugs, aiming to ensure the safety, effectiveness, and rationality of drug use by applying science and function in patient's care. Patients who have insurance are also entitled to get good service or quality, one of the government's insurance, namely BPJS. This study analyzes patient satisfaction with services seen from 5 dimensions, namely the dimensions of reliability, responsiveness, assurance, empathy, and tangibility. This research is an observational type with the cross-sectional method and was carried out by purposive sampling. Data collection was carried out in March-April 2020 using a questionnaire. Data analysis was carried out descriptively by comparing the satisfaction and expectation values ​​, which were then related to the range value to obtain the patient's satisfaction level. The results of this study of 51 respondents obtained an average level of satisfaction value of 0.85 (high) from the five dimensions, namely reliability of 0.86 (high), the responsiveness of 0.68 (sufficient), assurance of 0.90 (high), empathy is 0.94 (high), and reality is 0.91 (high).